1987
DOI: 10.1007/bf00581833
|View full text |Cite
|
Sign up to set email alerts
|

The effect of inorganic phosphate on the ATP hydrolysis rate and the tension transients in chemically skinned rabbit psoas fibers

Abstract: The role of orthophosphate ions (Pi) in crossbridge kinetics was investigated by parallel measurements of the ATP hydrolysis rate and tension transients in maximally activated, chemically skinned rabbit psoas fibers. The hydrolysis rate of the standard activation at 20 degrees C was measured at 1.25 nmole X s-1 X m-1 X fiber-1, which corresponds to the hydrolysis of 3 moles ATP per mole of myosin head per second. The isometric tension, stiffness extrapolated to the infinite frequency, and the ATPase rate progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
79
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(110 citation statements)
references
References 43 publications
30
79
1
Order By: Relevance
“…This confirms an earlier study in detail (19). Usefully, this pattern of coupling mirrors the P i sensitivity of phase 2 slow ; P i sensitivity is apparent in slow-(34) and medium-speed fibers (35), but not fast fibers (18,36). This correlation locates P i release before tension generation with step 6 reversible in all but fast fibers.…”
Section: L-jump Kinetics and The Cross-bridge Cyclesupporting
confidence: 86%
“…This confirms an earlier study in detail (19). Usefully, this pattern of coupling mirrors the P i sensitivity of phase 2 slow ; P i sensitivity is apparent in slow-(34) and medium-speed fibers (35), but not fast fibers (18,36). This correlation locates P i release before tension generation with step 6 reversible in all but fast fibers.…”
Section: L-jump Kinetics and The Cross-bridge Cyclesupporting
confidence: 86%
“…We are learning that a more complete contractile apparatus better recapitulates the cellular phenotype produced by mutations in regulatory proteins (11,20,32,34). As shown by Güth and Potter (18) and others (36,37), when ADP is added to the solution, the equilibrium shifts toward strongly bound crossbridge states, and the apparent Ca 2ϩ sensitivity increases. Others (18, 36 -39) have shown that adding P i to the solution shifts the equilibrium toward detached cross-bridge states and a decrease in the apparent Ca 2ϩ sensitivity.…”
Section: Discussionmentioning
confidence: 88%
“…It is of note that the lactate release is of equal magnitude at 3-4 and 7-8 min at 50 W. The magnitude of the anaerobic contribution is a minimum value as some accumulation of lactate may also occur at the 'steady-state' phase at this exercise intensity. The possibility exists that this anaerobic energy yield from glycolysis compensates for a reduction in free energy (AG) from ATP hydrolysis when increases take place in factors such as temperature and Pi and reduction in pH (Kawai, Guth, Winnikes, Haist & Ruegg, 1987; Cooke, Franks, Luciani & Pate, 1988). If this assumption is correct, one would have anticipated that the same would occur during the intense exercise, i.e.…”
Section: Discussionmentioning
confidence: 99%